(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2023)
In this paper, we introduce the concept of continuous g-fusion frame and K-g-fusion frame in Hilbert C^*-modules. Furthermore, we investigate some properties of them and discuss the perturbation problem for continuous K-g-fusion frames.